2012
DOI: 10.1111/j.2042-7158.2012.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

BND-12, a novel nonhaematotoxic naphthalimide derivative, inhibits tumour growth and metastasis of hepatocellular carcinoma

Abstract: BND-12 exerted potent effects against HCC in vivo and in vitro, importantly, it had no obvious systemic toxicity at the therapeutic dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Cell migration and invasion are the most prominent features of malignant cell behavior. Many reports [ 38 , 39 ] showed that naphthalimide derivatives could inhibit tumor cells migration and invasion in vivo. In this study, compound 3a inhibited migration and invasion of SMMC-7721 and HepG2 cells using scratch assay and transwell invasion assay in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Cell migration and invasion are the most prominent features of malignant cell behavior. Many reports [ 38 , 39 ] showed that naphthalimide derivatives could inhibit tumor cells migration and invasion in vivo. In this study, compound 3a inhibited migration and invasion of SMMC-7721 and HepG2 cells using scratch assay and transwell invasion assay in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Naphthalimides have been reported to serve as core scaffold for many antitumor, anti‐inflammatory, antidepressant, antiprotozoal, and antiviral agents, and some of which were found without obvious systemic toxicities at the therapeutic dose (Kamal, Bolla, Srikanth, & Srivastava, 2013; Xie et al, 2012). Therefore, in the current study, we rationally designed and developed a series of naphthalimide compounds, which combine Aβ aggregation inhibition, neutralization of oxidative stress and neuroprotection, as MTDLs against AD.…”
Section: Introductionmentioning
confidence: 99%